Association Between Indoor Environmental Conditions and Airborne Bacterial Counts in Inpatient Rooms at I.A. Moeis Regional Public Hospital, Samarinda: IN PRESS - Nur Nazliyatun Nada; Ayudhia Rachmawati; Riyan Ningsih; Blego Sedionoto; Vivi Filia Elvira (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Hospitals are highly vulnerable to indoor air pollution, particularly in inpatient rooms where interactions among patients, visitors, and healthcare workers may influence environmental sanitation and infection risk. This study aimed to assess airborne bacterial counts and indoor environmental conditions and to explore their associations in inpatient rooms at I.A. Moeis Regional Public Hospital, Samarinda. An exploratory cross-sectional environmental assessmentwas conducted in 7 rooms selected purposively based on room class and function. Airborne bacteria were measured using the Total Plate Count method, while environmental parameters included temperature, humidity, lighting, occupancy density, disinfection frequency, and ventilation conditions. Data were analyzed using univariate and correlation tests. The mean bacterial count was 317.86 CFU/m³, ranging from 98 to 397 CFU/m³, and no room exceeded the upper reference limit of 500 CFU/m³. The mean temperature was 25.5°C, above the recommended range, while mean humidity was 71% and reached 83%, exceeding the recommended range of 40–60%. Two rooms had lighting below 100 lux, and room-space compliance varied. Disinfection was performed twice daily. No significant associations were observed between bacterial counts and temperature, humidity, lighting, or occupancy density (p > 0.05). These findings should be interpreted cautiously because the small sample size (n = 7) limited statistical power. Hospitals should strengthen routine microbial monitoring, maintain ventilation and air-conditioning systems, assess airflow and air-exchange effectiveness, control temperature and humidity, manage occupancy, and consistently implement disinfection and environmental hygiene practices.